ANALISIS FENOMENA URBAN HEAT ISLAND BERDASARKAN TUTUPAN LAHAN DI KOTA PEKANBARU - Sasmita, Aryo; Darmayanti, Lita; Putra, Iqbal Perdana (Pusat Penelitian dan Pengembangan BMKG, 2023)
Pekanbaru City is the capital of Riau Province with a variety of very rapid development activities along with the increasing number of city residents, resulting in reduced vegetative land. This is the cause of the increase in surface temperature in Pekanbaru City, especially in the city center, which can accelerate the Urban Heat Island (UHI) phenomenon. The purpose of this study was to determine the distribution of surface temperature and identify the UHI phenomenon in Pekanbaru City. The research method is to identify the distribution of surface temperatures in the research period 2013-2018. Extraction of surface temperature comes from Landsat 8 imagery. The UHI phenomenon is seen from the temperature difference between the downtown area represented by Sukajadi Village and suburban areas, namely Kulim Village, Tebing Tinggi Okura, Muara Fajar, and Tuah Karya. The results showed that Pekanbaru City experienced the UHI phenomenon during the study period, because the temperature was already more than 30℃ and there was a temperature difference between the city center and the outskirts of the city that exceeded 3℃.